Unfolded Protein Response–Related Signature Associates With the Immune Microenvironment and Prognostic Prediction in Osteosarcoma - Zhang, Zhao; Liu, Xincheng; Cheng, Debin; Dang, Jingyi; Mi, Zhenzhou; Shi, Yubo; Wang, Lei; Fan, Hongbin (Frontiers in Genetics, 2022)
Background: Osteosarcoma is a highly malignant bone tumor commonly occurring in adolescents with poor 5-year survival. The unfolded protein response (UPR) can alleviate the accumulation of misfolded proteins to maintain homeostasis under endoplasmic reticulum stress. UPR is linked to the occurrence, progression and drug resistance of tumors. However, the function of UPR-related genes (UPRRGs) in disease progression and prognosis of osteosarcoma remains unclear. Methods: The mRNA expression profiling and corresponding clinical features of osteosarcoma were acquired from TARGET and GEO databases. Consensus clustering was conducted to confirm different UPRRGs subtypes. Subsequently, we evaluated the prognosis and immune status of the different subtypes. Functional analysis of GO, GSEA and GSVA was used to reveal the molecular mechanism between the subtypes. Finally, four genes (STC2, PREB, TSPYL2, ATP6V0D1) were screened to construct and validate a risk signature to predict the prognosis of patients with osteosarcoma. Result: We identified two subtypes according to the UPRRGs expression patterns. The subgroup with higher immune scores, lower tumor purity and active immune status was linked to better prognosis. Meanwhile, functional enrichment revealed that immune-related signaling pathways varied markedly in the two subtypes suggesting that UPR might influence the prognosis of osteosarcoma via influencing the immune microenvironment. Moreover, prognostic signature and nomogram models were developed based on UPRRGs, and the results showed that our model has excellent performance in predicting prognosis of osteosarcoma. qPCR analysis was also conducted to verify the expression level of the four genes. Conclusion: We revealed the crucial contribution of UPRRGs in the immune microenvironment and prognostic prediction of osteosarcoma patients, and provided new insights for targeted therapy and prognostic assessment of the disease.